Brucellosis: A Rare Cause of Febrile Neutropenia in a Child. Issue 10 (14th July 2022) - Cucuzza, Maria Elena; Garozzo, Maria Teresa; Coco, Marilena; Di Stefano, Vita Antonella
Abstract : We report a case of brucellosis-induced severe neutropenia in a 2-year-old girl who presented with a 2-week history of fever. On clinical examination, the patient was febrile with mild aphthous stomatitis. However, her general condition was stable, and systemic examination did not show involvement of any other organ. Laboratory test results revealed severe neutropenia, mild anemia, and an elevated serum C-reactive protein level. Flow cytometry of peripheral blood leukocytes revealed no malignancy, and blood film morphology was unremarkable except for mild microcytosis and hypochromia. Antineutrophil antibody and Coombs test results were negative. We administered intravenous cefuroxime; however, therapy was switched to meropenem plus clarithromycin because fever persisted for 5 days, despite treatment. On the 10th day after admission, Brucella serology tests showed positive results, and trimethoprim-sulfamethoxazole plus rifampicin therapy was prescribed for 8 weeks. The fever defervesced, and the child was discharged in a good state of health. Neutropenia persisted for several months but gradually resolved. Neutropenia, defined as an absolute neutrophil count (ANC) < 1.5 cells × 10 9 /L beyond the first year of life, is a benign transient condition associated with an intercurrent infection (usually viral illnesses or infections) in immunocompetent children. However, severe neutropenia (ANC < 0.5 × 10 9 /L) associated with fever necessitates hospitalization and administration of broad-spectrum antibiotics to avoid the high risk of sepsis, particularly in children. Brucellosis is rarely associated with hematologic abnormalities such as neutropenia. Early diagnosis of hematologic complications of brucellosis is essential for prompt initiation of specific and aggressive treatment.